Sentralisasi Pelaporan Rawat Jalan Berbasis Elektronik di Rumah Sakit X - Awaluddin, Mohamad Robby; Yunengsih, Yuyun; Abdussalaam, Falaah (Politeknik Negeri Jember, 2025)
The preliminary study revealed that the outpatient reporting system at Hospital X is still fragmented across individual polyclinics, with the reporting process conducted manually using Microsoft Excel. This condition results in a time-consuming report compilation process. The aim of this study is to develop a centralized outpatient reporting system integrated within a single information system. This centralization is expected to enhance the effectiveness of medical record staff in compiling outpatient reports. The research employed a research and development (R&D) method with a systematic approach to improve the existing system. The information system was designed using the waterfall method and developed with Visual Studio Code software. The outcome of this study is an outpatient information system equipped with various features to support the compilation of outpatient service reports. Based on the study’s findings, Hospital X has the potential to further develop this reporting system to be more optimal and fully integrated with the existing Hospital Management Information System (HMIS).